PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN LOAN TO DEPOSITRATIO (LDR) TERHADAP PENYALURAN KREDIT PADA BANK RAKYAT INDONESIA TBK - Ahmad Fran M Hrp; Toti Indrawati; Any Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to determine the effect of the Capital Adequacy Ratio (CAR) and the Loan to Deposit Ratio (LDR) Against Lending at Bank Rakyat Indonesia Tbk. This study uses secondary data obtained from the financial statements of Bank Rakyat Indonesia Tbk. This research was conducted nationally in the period 2011 to 2015 and the data presented in the form Quarterly.This study uses a quantitative method, and analyzed using multiple linear regression analysis using a computer application program SPSS 17.0.The study consists of two independent variables (Capital Adequacy Ratio and Loan to Deposit Ratio) and a dependent variable (Lending). The results obtained are the Capital Adequacy Ratio (CAR) and the Loan to Deposit Ratio (LDR) simultaneously influence Lending at Bank people of Indonesia Tbk with a significance level of 5% was obtained value of the probability of F statistic <α (0.05), ie 0.000> 0.05, Partially Capital Adequacy Ratio (CAR) Significant Impact on Lending while variable Loan to Deposit Ratio (LDR) not has the significant impact to the credit distribution. Variation factors that influence Lending explained by Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) together influential of 83.4% (R2 = 0.834). This means that approximately 83.4% Lending explained by the variable Capital Adequacy Ratio and Loan to Deposit Ratio simultaneously.Keywords: Capital Adequacy Ratio (CAR), loan to Deposit Ratio (LDR) and Lending).